Pengaruh Social Media Marketing dan Penentuan Lokasi terhadap Minat Beli Rumah di Komplek Bumi Indah Parahyangan - Febriyanti, Gina; Nurtjahjadi, Edi (Universitas Batanghari, 2024)
The aim of this research is to examine the influence of social media marketing and location determination on interest in buying a house in the Bumi Indah Parahyangan Complex in West Bandung Regency. The research confirmed that the instrument utilized had successfully undergone assessments for validity and reliability. This tool was employed to gather data from respondents, specifically individuals visiting the Bumi Indah Parahyangan Complex, In this study, the subject under assessment comprised 90 respondents. The data collection method employed was a cross-sectional or one-shot study. Analysis was conducted through classic assumption tests and multiple linear regression using SPSS version 25 tools. Of the two proposed research hypotheses, one of them is supported by empirical data. The findings of this research indicate that social media marketing can influence location determination on purchasing interest.